Um estudo em cardiopatas submetidos à revascularização do miocárdio: ansiedade e depressão - Pereira, Camila [UNESP] (2015)
The growing association between depression and increase in mortality after coronary bypass graft sugery, combined with life experiences following hospital stay, have motivated us to research about the frequency of depressive and anxiogenic factors in heart disease patients who show the need for such sugery. Theerfore, the purpose of this study was to explore emotional characteristic of patients who undergone coronary bypass graft surgery and then to examine anxiety and depression symptoms developed by concepts previously adopted from reports from other patients, from the doctors' positions, from the nurses communications, and other sources. Out of the chronic diseases, depression and cardiovascular disease are considered to have the most impact on the patient's quality of life. The symptoms of anxiety and depression are related to the repeated occurrence of acute myocardial infarctions, death by cardiac diseases, prolonged hospitalization and functional loss after acute myocardial infarction. Moreover, they can delay the healing and welfare of the patients, such as, lack of personal interests and social relationships, which can aggravate their clinical diagnosis. There were participants in the research, both sexes and ages, ranging from 36 to 70 years old. All participants had suffered acute myocardial infarcton and were admitted to the Cardiology Sector of the Hospital de Base de Bauru - SP/FAMESP for coronary bypass graft surgery. The instruments used during the research were: the Beck Depression Inventory II; the Hospital Anxiety and Depression Scale - HAD and the Structured Clinical Interview for Mental Disorders I of DSM IV - SCID IV, seeking to evaluate the presence and severity of symptoms of anxiety and depression, as well as possible disorders. The instruments were applied accordingly to technical recommendations and in individual sessions. The data were coded according to the proposition of each instrument. For the analyses...